COMPARISON OF SINGLE BOLUS NOREPINEPHRINE WITH PHENYLEPINEPHRINE FOR PREVENTION OF HYPOTENSION DURING CESAREAN SECTION UNDER SPINAL ANESTHESIA - Pervaiz, Mishal; Raja Mushtaq Hussain,; Mudasir Saleem, Muhammad (Journal of Ayub Medical College Abbottabad, 2026)
Background: Hypotension remains the main concern following spinal anesthesia in patients planned for cesarean section. A no of pharmacological agents has been used prophylactically to prevent hypotension in past. Norepinephrine and phenylepinephrine are the two most commonly used agents. Aim of this study was to evaluate the effectiveness of these two agents used as single bolus for prevention of hypotension during cesarean section under spinal anesthesia. Methodology: This Quasi-experimental study was conducted in Department of anesthesia, Pak Rangers Teaching Hospital Lahore. A total of 180 patients (90 in each group) fulfilling the inclusion criteria were included in this study. Patients were divided into two groups by using lottery method. Group-A (PE group) received phenylepinephrine bolus while Group-B (NE group) received norepinephrine bolus under spinal anesthesia. Blood pressure (primary outcome) and heart rate (secondary outcome) was recorded for 20 minutes at five-minute interval. Incidence of hypotension and bradycardia was recorded in both groups. Presence of hypotension alone or with bradycardia in both groups was treated with intravenous crystalloid bolus @ 10ml per kg body weight. Persistent hypotension with bradycardia despite crystalloid bolus treated with a rescue bolus of intravenous atropine 0.6 mg was considered the endpoint. Results: 33.3% (n=30) in PE Group while 18.9% (n=17) in NE Group developed hypotension with p value of 0.04. Similarly, 20% (n=18) in PE Group as compared to 4.4% (n=4) in NE Group had bradycardia showing statistically significant difference between the two groups with p value of 0.02. Regarding need of rescue atropine bolus, n=5 (5.5%) in PE Group while n=1 (1.1%) in NE Group required it with calculated p value of 0.09. Conclusion: We concluded that prophylactic bolus of norepinephrine was more effective than phenylepinephrine in prevention of post spinal hypotension and bradycardia during cesarean section with better maintenance of systolic blood pressure and heart rate. Keywords: Hypotension, Norepinephrine, Phenylepinephrine, Spinal anesthesia.